Design Web-Based of Hajj Registration System for Iraq - Salih, Ali Khalil (2012)
In the 21st century, the internet and web-Based systems represent the primary strategic resources in the world. Majority population of the world use it every day and everywhere without exception. This study proposes to design a web-based registration for pilgrims in Iraq. In order to give all Iraqi citizens accessibility to make the registration available even properly, easily, and without tiredness. The main problems facing the organizers of this event in Iraq are due to two issues. The first one is the manual usage it is difficult to trace if hajj registered more than once. Secondly, it will take a long time for the potential pilgrims to know about the date and schedule for travel. This system will use the national number and passport number to login in the system and to register with prevents duplication happen. The pilgrim would also be able to be connected to SMS to know date and time for travel. The system will be developed by using UML to analysis and JSP with SQL server 2008 to create the registration system. Finally, it is very important to design an electronic system. That will enable the Iraqi citizens to register in the system in anytime and anywhere toward give more accurate information.